2016
DOI: 10.1259/dmfr.20150226
|View full text |Cite
|
Sign up to set email alerts
|

Radiographic methods used before removal of mandibular third molars among randomly selected general dental clinics

Abstract: Objectives: To assess radiographic methods and diagnostically sufficient images used before removal of mandibular third molars among randomly selected general dental clinics. Furthermore, to assess factors predisposing for an additional radiographic examination. Methods: 2 observers visited 18 randomly selected clinics in Denmark and studied patient files, including radiographs of patients who had their mandibular third molar(s) removed. The radiographic unit and type of receptor were registered. A diagnostica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 16 publications
1
16
0
Order By: Relevance
“…6,[8][9][10][11][12][13] Another reason to perform CBCT may be to clarify the presence of pathology in relation to the third molar, which could be decisive for removal, even in lack of patient symptoms. This study has focused on the association between findings in PAN and CBCT in terms of resorption and marginal bone loss in/at the distal surface on the second molar and increased periodontal space around the crown of the third molar.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…6,[8][9][10][11][12][13] Another reason to perform CBCT may be to clarify the presence of pathology in relation to the third molar, which could be decisive for removal, even in lack of patient symptoms. This study has focused on the association between findings in PAN and CBCT in terms of resorption and marginal bone loss in/at the distal surface on the second molar and increased periodontal space around the crown of the third molar.…”
Section: Discussionmentioning
confidence: 99%
“…Intraoral imaging is an alternative, but it has been shown that in around 25-36% of the cases, the full third molar and adjacent anatomical structures are not imaged by this method. 5,6 The debate on when to perform CBCT prior to surgical removal of mandibular third molars continues. Recently, is has been shown in a prospective clinical study that CBCT changed the treatment of the patients only in a minority of cases.…”
Section: Introductionmentioning
confidence: 99%
“…From the patient's point of view, the total price for surgical removal of a mandibular third molar in DK most probably will double if CBCT imaging becomes the routine. 6,22 The consequences for the treatment accept by the mostly young patients are not predictable. Some patients would maybe avoid proper treatment owing to the increase in costs.…”
Section: Discussionmentioning
confidence: 99%
“…12 After 2007, many researchers analyzed the role of CBCT in revealing the position of the third mandibular molars in relation to anatomical landmarks while others focused on the economical and health implications of the use of CBCT. [13][14][15] In 2015, Maglione et al described a CBCT classification of mandibular impacted third molars, to present the correlation between anatomical variations and clinical practice and help surgeons choose the correct surgical technique. This classification follows the different aspects of the position of the mandibular canal reported to the roots of the impacted tooth, highlighting the difficulty in cases when the mandibular canal runs between the roots touching them or when it runs between fused roots.…”
Section: Impacted Mandibular Third Molarsmentioning
confidence: 99%
“…1). 15,17 Impacted Maxillary Third Molars Using CBCT for treatment planning of impacted maxillary third molars has been analyzed in different studies, but the latest retrospective study conducted by a team of experienced oral and maxillofacial radiologists concluded that a CBCT examination is indicated when external root resorption of the second molar is suspected on panoramic radiography. Hermann et al reported that CBCT findings regarding the second maxillary molar's severe root resorption (►Fig.…”
Section: Impacted Mandibular Third Molarsmentioning
confidence: 99%